ANALISIS CHI-SQUARE HUBUNGAN SARANA SANITASI DASAR DENGAN KEJADIAN DIARE PADA BALITA DI PERUMAHAN PTPN V SEI SIASAM - Novrika Silalahi (Jurnal Penelitian Kesmasy, 2022)
Research background basic sanitation facilities are directly related to health problems, especially environmental health problems. Basic sanitation facilities which includes healthy latrine facilities, clean water facilities, waste management facilities and waste water disposal facilities. The purpose of the research is to find out relationship between healthy latrine facilities and the incidence of diarrhea, to determine the relationship between clean water facilities with the incidence of diarrhea, to determine the relationship between facilities waste management with the incidence of diarrhea, to determine the relationship between waste water disposal. The research method in this study uses quantitative descriptive with cross sectional research design. population in This study is a housing PTPN V as many as 1880 families. sample taken using a systematic sampling technique, namely the sampling technique sample based on the order of toddlers who become the population that has been given the serial number of the sample is 45 families. statistical test using chi square test. The results showed that there was a relationship between healthy latrine facilities and incidence of diarrhea (p = 0.181), there is a relationship between clean water facilities and the incidence of diarrhea (p=0.510), there is a relationship between waste processing facilities and the incidence of diarrhea (p = 0.039), there is a relationship between sewage drainage facilities and the incidence of diarrhea (p = 0.746) is recommended to parents or mothers to increase its role in the provision of basic sanitation facilities, which include: healthy latrine facilities, clean water facilities, waste management facilities and waste water disposal (SPAL), to avoid disease.